Global trends of rapeseed grain yield stability and rapeseed-to-wheat yield ratio in the last four decades - Rondanini, Deborah Paola (2012)
Increases in crop yields are important to ensure food supply for humanity. Global yield trends have been analyzed considering public national average data, mainly for cereals but not for rapeseed. As rapeseed and wheat compete for land in crop rotation, it is also important to know how the rapeseed-to-wheat yield ratio is modified in different environments so as to make rapeseed an attractive alternative for farmers around the world. The present study analyzed historical records of rapeseed from FAO determining yield stability trends over the last 40yr, as well as rapeseed competitiveness compared to wheat. Twelve countries representing a wide range of environments and farming systems were taken into account. Regressions were fitted to the rapeseed yield/time relationships and residuals of these regressions were used to evaluate trends in yield stability. Results showed a global rapeseed yield gain of 27kgha -1yr -1 along the past 40yr, although fluctuating among decades. In relative terms to 1970, world rapeseed yield increased 3.4%yr -1. Yield gain in different countries varied from 15 to 40kgha -1yr -1, exhibiting linear, bi- or tri-linear yield trends. Opposite yield trends were observed for Chile and the UK, with sustained yield gain for the former and leveling off for the latter since the mid 1980s. This does not seem to be related to the supply of environmental resources (both countries yielding >3000kgha -1). A high variability was detected in national yields (0-750kgha -1 or 0-60% of yield) and yield stability did not increase over the last 40yr in any country. Rapeseed and wheat yields, expressed in relative terms to their values for 1970, increased in a similar proportion over the last four decades. Global rapeseed-to-wheat ratio ranged 40-60% over the last 40yr, but rapeseed yields can increase up to 80-100% with respect to wheat in poor environments for wheat (<2000kgha -1), leveling off around 40% in high wheat yields environments (>4000kgha -1). It was concluded that rapeseed yields have increased steadily in the last 40yr in most studied countries, the yield gain was not accompanied by greater yield stability, and rapeseed competitiveness compared to wheat is at least 40-50% in environments with good supply of resources. © 2011 Elsevier B.V.